The roles of cancer stem cell-derived secretory factors in shaping the immunosuppressive tumor microenvironment in hepatocellular carcinoma - Muliawan, Gregory Kenneth; Lee, Terence Kin-Wah (Frontiers in Immunology, 2024)
Hepatocellular carcinoma (HCC) is one of the most prevalent malignancies worldwide and has a poor prognosis. Although immune checkpoint inhibitors have entered a new era of HCC treatment, their response rates are modest, which can be attributed to the immunosuppressive tumor microenvironment within HCC tumors. Accumulating evidence has shown that tumor growth is fueled by cancer stem cells (CSCs), which contribute to therapeutic resistance to the above treatments. Given that CSCs can regulate cellular and physical factors within the tumor niche by secreting various soluble factors in a paracrine manner, there have been increasing efforts toward understanding the roles of CSC-derived secretory factors in creating an immunosuppressive tumor microenvironment. In this review, we provide an update on how these secretory factors, including growth factors, cytokines, chemokines, and exosomes, contribute to the immunosuppressive TME, which leads to immune resistance. In addition, we present current therapeutic strategies targeting CSC-derived secretory factors and describe future perspectives. In summary, a better understanding of CSC biology in the TME provides a rational therapeutic basis for combination therapy with ICIs for effective HCC treatment.